1997
DOI: 10.1093/oxfordjournals.jhered.a023152
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic Analysis of C-Banded Chromosomes of Diploid Alfalfa: Medicago sativa ssp. caerulea and ssp. falcata and Their Hybrid

Abstract: Chromosomes of two diploid (2n = 2x = 16) subspecies of Medicago sativa ssp. caerulea and ssp. falcata and their hybrid were studied by C-banding. This study was undertaken to improve the C-banding technique for alfalfa chromosomes, develop a C-banded karyotype of the ssp. caerulea and ssp. falcata, and determine if the same C-banding technique could be used to identify parental chromosomes in hybrids. The chromosomes of ssp. falcata have only centromeric bands and thus individual chromosomes could not be iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…caerulea [Bauchan and Hossain, 2001]) and M. sativa subsp. falcata (Bauchan and Hossain, 1997). Thus, while these two results are limited in their scope, they suggested that chromosomal differences could exist between subspecies and that these could affect the progeny of SFC.…”
Section: Resultsmentioning
confidence: 99%
“…caerulea [Bauchan and Hossain, 2001]) and M. sativa subsp. falcata (Bauchan and Hossain, 1997). Thus, while these two results are limited in their scope, they suggested that chromosomal differences could exist between subspecies and that these could affect the progeny of SFC.…”
Section: Resultsmentioning
confidence: 99%
“…glomerata , which they considered to be the ancestor of "caerulea" and "falcata." These two diploid taxa also have cytogenetic differences as shown in their C-banding karyotypes ( Bauchan and Hossain 1997 ).…”
mentioning
confidence: 99%
“…coerulea and subsp. falcata by their unique banding patterns using C‐banding (Bauchan and Hossain, 1997, 1999a). Falistocco et al (1995) reported the first C‐banded karyotype of tetraploid alfalfa based on the Italian cultivar ‘Turrena’.…”
mentioning
confidence: 99%